PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN SIMULASI PHET UNTUK MENINGKATKAN HASIL BELAJAR MATERI USAHA DAN ENERGI PADA PESERTA DIDIK KELAS XI SMA MUHAMMADIYAH JAYAPURA - Susmita, Nilam; Budiarti, Indah Slamet (Papua Journal of Physics Education, 2024)
This study aims to determine the effect of the application of the PhET simulation-assisted Discovery Learning model on improving business and energy learning outcomes in class XI students of SMA Muhamadiah Jayapura. This type of research is a quantitative research with experimental methods, Pre-Experimental design with the type of One Group Pre-Test Post-Test Design. The population in this study were all students of class XI SMA Muhamadiah Jayapura. The sampling technique used is Cluster Random Sampling. Thus, the sample set was class XI.1 as the control class as many as 34 students, XI.2 as the experimental class as many as 31 students and class XI.3 as many as 28 students as the instrument testing class as many as 28 students. The research instrument used was a multiple choice instrument consisting of 20 questions. The results of research and data processing in the experimental class RPP I, RPP.II, combined RPP, respectively, the average value of Pre-Test 28.71 < Post-Test 77.74, Pre-Test 32.90 < Post-Test 82.26, Pre-Test 31.12 < Post-Test 80. Nilan N-Gain in experimental class and control class RPP I, RPP II and combined RPP respectively obtained experimental N-Gain 0.70 > N-Gain control 0.57, experimental N-Gain 0.74 > N-Gain control 0.61 , Experimental N-Gain 0.72 > Control N-Gain 0.58. The results of the different tests on RPP I, RPP.II, combined RPP obtained the same value, namely Sig (2-Tailed) 0.000. The results of the data processing indicate that there is an increase and difference in student learning outcomes in the matter of effort and energy after using the PhET simulation-assisted Discovery Learning model.